Numerical Study of the Aerodynamic Interference of Rotors Imposed on Fuselage for a Quadcopter - Yifei Zhu (IEEE, 2021)
This paper investigates the transient aerodynamic interference of rotors imposed on fuselage for a quadcopter through Computational Fluid Dynamics (CFD) simulations. The numerical study of transient effects due to rotor rotation is enabled by sliding mesh which defines the rotation domains encompassing rotor blades. The results show that the interference effects of rotor change the aerodynamic forces of the fuselage, causing about 67% in-crease in lift, 13% increase in drag, and 90% increase in pitching up moment on average. The variations of fuselage lift are associated with the pressure distribution changes due to rotors rotation, the high-pressure areas and low-pressure areas over the rotor projects on the arms of the quadcopter causing periodical abrupt changes on the lift, drag and pitching moment.